Comparative analysis of functional capabilities and special working ability of men and women, specializing in 800 m and 1500 m running - Kalytka, S.; Roda, O.; Ierko, I.; Panasiuk, O.; Kasarda, O.; Hrebik, O.; Faidevych, V.; Liannoi, M. (Journal of Physical Education and Sport, 2018)
The problem of increasing the efficiency of female athletes` training, in accordance with the functional state in different phases of the menstrual cycle, as well as the responses of adaptation mechanisms to specific loads; special performance level of women and men, specializing in running at 800m and 1500m, has been studied. Methods and research organization: analysis and generalization of scientific and methodical literature; questionnaire survey; pedagogical experiment; biomedical and statistical theory methods. The survey involved 13 women and 10 men, specializing in running at 800m and 1500m, at the age of 17-24, who qualified as Candidate Master of Sports (ÑMS), I and II skill-categories. The state of all athletes` health was within the limits of the physiological norm. Women's studies have been conducted, taking into account phases of the menstrual cycle, simultaneously, men have been examined too. We have noted the highest rates of special working ability among women, as evidenced by the results of female athletes` running of 4*400m training sessions, among female athletes (CMS and I skill-category) in the postmenstrual and postovulatory phases of the menstrual cycle (MC), which surpassed the results in comparison with the menstrual, ovulatory and premenstrual phases; the best results among the female athletes of the II skill-category were recorded in the postmenstrual (p<0,05) and postovulatory (p<0,05) phases of the MC, the lower running outcome was in the premenstrual, menstrual and ovulatory phases of the MC. The adaptation reactions of the women bodies to the specific activities, aimed at manifestation of anaerobic endurance, are characterized by an optimal functional state in the postovulatory and postmenstrual phases, compared with the menstrual, ovulatory and premenstrual phases of the MC. It was determined that among the CMS and I skill-category male athletes, the best result of running 4*400m training session was in the third and fifth micro cycles, somewhat lower result was in the first and second microcycles, and it decreased in the fourth macrocycle; Athletes of the II skill-category had lower results in the second (p<0.05) and fourth, growing in the third and fifth micro cycles. The adaptation reactions of the male bodies to the specific activities, aimed at manifestation of anaerobic endurance, are characterized by an optimal functional state in the first, second, third and fifth micro cycles, with the slight decrease in the fourth micro cycle.